2006
DOI: 10.1080/10495390600957191
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Use of Antibiotic Growth Promoters in Diets Fed to Weanling Pigs: Dietary Tools, Part 2

Abstract: Diets formulated to maximize performance of weanling pigs need to support the development of intestinal tissue, support intestinal colonization with beneficial, mainly lactic acid-producing bacteria, and support development of the intestinal and overall immune system. This objective is not likely to be achieved using one single strategy, but there is strong evidence that diets formulated with cereal grains other than corn, with a low concentration of crude protein and with the use of direct-fed microbials, wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 73 publications
1
68
0
5
Order By: Relevance
“…Low-protein diets for weaned pigs level in weaned pig diets could result in a deficiency of other indispensable AA apart from lysine, methionine1 cysteine, threonine and tryptophan (Figueroa et al, 2002;Stein and Kil, 2006). Since most indispensable AA are not commercially available, formulation of weaned pig diets to be moderately low in CP should be done carefully.…”
Section: --mentioning
confidence: 99%
“…Low-protein diets for weaned pigs level in weaned pig diets could result in a deficiency of other indispensable AA apart from lysine, methionine1 cysteine, threonine and tryptophan (Figueroa et al, 2002;Stein and Kil, 2006). Since most indispensable AA are not commercially available, formulation of weaned pig diets to be moderately low in CP should be done carefully.…”
Section: --mentioning
confidence: 99%
“…Herbs and spice extracts have been used extensively in different parts of the World to treat a variety of human diseases (Stein and Kil, 2006). Gastrointestinal disorders have been treated with a number of different plant extracts including garlic, peppermint, chamomile or aloe (Amagase et al, 2001;Akerreta et al, 2007;Rodriguez-Fragoso et al, 2008).…”
Section: Plant Extractsmentioning
confidence: 99%
“…Some feed additives, such as prebiotics, probiotics and some other substances, have been studied with regard to managing the health of weaning piglets (Lalles et al, 2007). Among others, the use of probiotics such as lactobacilli and bifidobacteria has been proposed as the most promising approach for maintaining or improving animal health (Stein and Kil, 2006;Lalles et al, 2007). It has been reported that feeding certain probiotic strains to pigs could improve growth performance, prevent the growth of pathogenic bacteria and reduce the incidence of diarrhea (Shu et al, 2001;Gardiner et al, 2004;Taras et al, 2006;Casey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that feeding certain probiotic strains to pigs could improve growth performance, prevent the growth of pathogenic bacteria and reduce the incidence of diarrhea (Shu et al, 2001;Gardiner et al, 2004;Taras et al, 2006;Casey et al, 2007). At the same time, feeding an FLD prepared with the use of bacteria, such as lactic acid bacteria, has also been shown to improve pig performance and to reduce the number of enteric pathogens (Canibe and Jensen, 2003;Stein and Kil, 2006). These positive influences may be due to the low pH, high short-chain fatty acid content and high lactic acid bacteria content of the FLD.…”
Section: Introductionmentioning
confidence: 99%